Mini DNA barcodes reveal the details of the foraging ecology of the largehead hairtail, Trichiurus lepturus (Scombriformes: Trichiuridae), from São Paulo, Brazil - Boza, Beatriz R. [UNESP]; Cruz, Vanessa P. [UNESP]; Stabile, Gustavo; Rotundo, Matheus M.; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (FapUNIFESP (SciELO), 2022)
The largehead hairtail, Trichiurus lepturus, is an opportunistic, voracious, and piscivorous predator. Studies of fish feeding behavior based on the analysis of stomach contents are limited by the potential for the visual identification of the ingesta. However, molecular tools, in particular DNA barcoding, have been used successfully to identify stomach contents. When morphological analyses are not possible, molecular tools can precisely identify the components of the diet of a fish based on its stomach contents. This study used mini barcoding to identify food items ingested by T. lepturus off the northern coast of São Paulo State, Brazil. Forty-six sequences were obtained and were diagnosed as belonging to six different fish species: Pimelodus maculatus, Paralonchurus brasiliensis, Isopisthus parvipinnis, Opisthonema oglinum, Harengula clupeola, and Pellona harroweri or as belonging to the genera Lycengraulis and Sardinella. Trichiurus lepturus is an opportunistic predator that will exploit an available prey of an appropriate size. The results indicate that these fish migrate to warmer waters, such as those found in estuarine environments, at certain times of the year, where they exploit prey species that reproduce in this environment. One example was Pimelodus maculatus, which was the prey species most exploited based on the analysis of the material collected.
Keywords: COI gene; Largehead hairtail; Mini-barcode; Molecular tool